Launching of the Anaemia Research Peruvian Cohort (ARPEC): A multicentre birth cohort project to explore the iron adaptive homeostasis, infant growth and development in three Peruvian regions - Montag D. (2021)
Funding This project is supported by the Medical Research Council—MRC grant number MR/S024654/1 and by the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica—FONDECYT, grant number 033-2019. AJP is funded by the Wellcome Trust (108065/Z/15/Z).